Ethnomedicinal plants used for digestive system disorders by the Karen of northern Thailand - Kornkanok Tangjitman (2018)
© Tangjitman et al.; licensee BioMed Central. Background: Digestive system disorders have a substantial effect on worldwide morbidity and mortality rates, including in Thailand, where the majority of the rural areas have a lack of proper sanitation and awareness about disease prevention. This has led to the prevalence of different types of digestive diseases. Karen people in Thailand still use medicinal plants as first aid remedies in treating these diseases. Therefore, this study aimed at documenting the plants used to cure and prevent different types of digestive system disorders by Karen people of Chiang Mai Province, northern Thailand. Methods: Ethnomedicinal data were collected from six key informants and 172 non-specialist informants regarding their traditional knowledge of medicinal plants. Quantitative approaches were used to determine Use Value (UV), Informant Consensus Factor (ICF) and Fidelity Level (FL) values. Results: The study revealed that 36 medicinal plant species belonging to 31 genera and 24 families were used to treat digestive system disorders. The most prevalent plant families were Zingiberaceae (6 species), Euphorbiaceae (4 species) and Fabaceae (4 species). Leaves were the most commonly used plant part accounting for 32.6% of the plants, followed by the bark (18.6%). About 60% of the administrations were given orally by potion (60%) and consumption as food was also indicated (14%). The highest ICF values were recorded for carminative disorders, stomachaches, geographic tongue, constipation, appetite stimulants and food poisoning (1.00 each) indicating the best agreement among the informants knowledge of medicinal plants that were used to treat aliments in these categories. The highest fidelity level values were recorded for Punica granatum (100.00), Psidium guajava (95.45), and Gymnopetalum integrifolium (90.91) showing conformity of knowledge on species with the best healing potential. Conclusion: Medicinal plants still play an important role among Karen culture. The present information on these medicinal plants, which have high UV and FL values, may serve as the baseline data to initiate further research for the discovery of new compounds and the biological activities of these potential plant remedies. Further research on these plants may provide some important clues for the development of new drugs for the treatment of digestive system diseases.